Review of the current ongoing clinical trials exploring the possible anti-anxiety effects of cannabidiol - Rhenu Bhuller; Walter K. Schlage; Julia Hoeng (BMC, 2024)
Abstract Background Anxiety disorders (ADs) are a complex group of mental disorders and majorly contribute to the global health-related burden. Symptoms and clinical management differ widely depending on the specific diagnosis. There is a need for new, more effective pharmacological treatments for these patients as many patients do not respond to treatment and treatment is not available for several types of AD. The increased interest in the potential effects of cannabidiol (CBD) on symptoms of AD has led to several preclinical and clinical studies that suggest that CBD may be effective in some patients with AD. However, it remains unclear whether and how CBD can be used in the clinical management of ADs due to a lack of sufficiently robust clinical evidence. Comparative evaluation This narrative review provides a critical analysis of the current state of the art for ADs and summarizes six recently completed and 22 currently ongoing clinical trials investigating the effects of CBD on ADs or anxiety. The aim was to examine whether the ongoing trials are likely to provide the necessary solid evidence, or whether new studies with more robust design parameters can help to overcome the prevailing lack of solid clinical data for this CBD indication. Most of the trials reviewed are considered exploratory and do not focus on specific types of clinical anxiety or ADs as the primary condition studied. Participant numbers, CBD dose, treatment duration, and CBD formulation vary widely among the studies, and all but two are single-center studies. Conclusion For an effective clinical management of ADs using CBD, there is a need for sufficiently powered and appropriately designed clinical trials (RCT, multicenter, defined doses and exposure monitoring, robust primary outcomes) investigating the effect of CBD in specific ADs, such as social anxiety disorder and panic disorder, or in post-traumatic stress disorder.